Research on Crushing Concrete Members by High-Voltage Pulse Discharge Technology - Xiaodong Wang; Jiaxu Du; Ningjing Li (Advances in Civil Engineering)
High-voltage pulse discharge (HVPD) is an energy-saving, efficient, and green technique, which has broad prospects in concrete crushing. The finite element models of the concrete beam, slab, and column segments were established with ANSYS/LS-DYNA finite element software. Based on the principle of equal impact pressure, the shock wave generated by the fuse explosion caused by HVPD of 50 kJ is equivalent to the impact load of explosive blasting, and the stress of concrete beam segment was analyzed. The finite element models of the concrete beam sections were established to investigate the influence of diameter and spacing of the holes on the crushing effect of concrete beam segments. The width × height of each beam segment is 400  mm × 800  mm, and there are six types of beam segment length: 600 mm, 700 mm, 800 mm, 900 mm, 1000 mm, and 1100 mm. Two holes are drilled vertically on the surface of the width × length of each beam segment. The spacing of holes corresponding to beam segments of each length type is 200 mm, 300 mm, 400 mm, 500 mm, 600 mm, and 700 mm, respectively. The hole depth of each beam segment is 650 mm, and there are three types of aperture: 30 mm, 50 mm, and 70 mm. The analysis results show that the crushing effect of concrete beam segments increases with the increase of aperture and the decrease of hole spacing. According to the crushing effect of the beam segments, the aperture of 50 mm, the spacing of 400 mm, and the hole end (edge) spacing of 250 mm were determined as the optimal hole layout scheme. The finite element models of concrete slabs and columns were established. The square concrete slab thickness is 140 mm and side length is 700 mm, 800 mm, and 900 mm, respectively. Double-row holes were arranged in the slabs and the aperture is 50 mm and the hole spacing is 200 mm, 300 mm, and 400 mm, respectively. The section sizes of concrete columns are 500  mm × 500  mm, 600  mm × 600  mm, and 700  mm × 700  mm, respectively, and the aperture is 50 mm and the hole distance is 400 mm. According to the results of analysis, the optimal hole distribution scheme of concrete slab and column is chosen as the aperture of 50 mm and hole distance of 400 mm. The principle of the layout of multirow holes is that the spacing of row is not more than 400 mm, and the margin is not more than 250 mm.